2022
DOI: 10.1021/acsami.2c02249
|View full text |Cite
|
Sign up to set email alerts
|

Homogenizing Li2CO3 Nucleation and Growth through High-Density Single-Atomic Ru Loading toward Reversible Li-CO2 Reaction

Abstract: The high activation barrier and sluggish kinetics of Li2CO3 decomposition impose a severe challenge on the development of a Li-CO2 battery with high Coulombic efficiency. To tackle this issue, herein we devise a novel synthetic tactic by combining electrostatic assembly with in situ polycondensation to obtain a single-atomic Ru catalyst of high density up to ∼5 wt %. When deployed to the CO2 cathode, the catalyst delivered an extraordinary capacity of 44.7 Ah g–1, an ultralow charge/discharge polarization of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Further efforts were devoted to investigating the catalytic activity of Ru SACs in LCBs, and these studies also confirmed the superior battery performance of SACs compared with that of nanoparticles. 50,191…”
Section: Typical Sacs Applied In Lcbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further efforts were devoted to investigating the catalytic activity of Ru SACs in LCBs, and these studies also confirmed the superior battery performance of SACs compared with that of nanoparticles. 50,191…”
Section: Typical Sacs Applied In Lcbsmentioning
confidence: 99%
“…Recently, single-atom catalysts (SACs) with fully exposed atom surfaces and extremely high catalytic activity were introduced into LABs, serving as a powerful strategy in boosting the formation/decomposition process of discharge products and taming the bothersome lithium dendrite with significant enhancement in the battery performance, such as reduced overpotential, improved security, increased capacity and enhanced cyclability 22,[42][43][44][45][46][47][48][49][50][51][52][53][54] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Baek et al adopted Ru nanoparticles as the cathode and a nitrate-based molten salt as the electrolyte to explore the role of NO 2 À in the decomposition mechanism of surface , as shown in eqn (35).…”
Section: Charge Mechanism Of Li-co 2 Batteriesmentioning
confidence: 99%
“…34 However, although noble metal catalysts exhibit excellent electrochemical activity and catalytic stability, their high price, chemical vulnerability and low reserves limit their large-scale applications. 35 Alternatively, carbon-based catalysts have attractive advantages such as low cost, high abundance, and tunable morphology and structure, but their unsatisfactory catalytic activity and stability limit their development. 36 Therefore, researchers are devoted to selecting and optimizing abundant, highly active, and durable transition metal catalysts to enhance the catalytic performance of Li–CO 2 batteries.…”
Section: Introductionmentioning
confidence: 99%
“…As a rising star, single-atom catalysts (SACs) are also of interest to researchers in the field of Li–CO 2 batteries. 177–180 The main reasons are: (1) the isolated metal sites have nearly 100% atomic utilization; (2) SACs have fully exposed active sites. These two points together determine the outstanding catalytic activity of SACs.…”
Section: Introductionmentioning
confidence: 99%